The Effectiveness of Home and Hospital Enteral Nutrition: A Preliminary Study - Moretta Damayanti; Yoga Devaera; Aria Kekalih (Majalah Kedokteran Sriwijaya, 2019)
Home enteral nutrition (EN) at dr. Mohammad Hoesin Hospital (RSMH) was rare. Its acceptability and effectiveness were not known. This study was aimed to determine the effectiveness of home EN compared with EN for hospitalized patients as the control group. We conducted a preliminary quasi-experimental study with anthropometric measurements every seven days until the twenty-eighth day. There were 15 subjects for each group. The acceptability rate of home EN was 100%. The mean of initial weight for height (WHZ T0) between the control group and home EN group was -2.83 (2.49) vs -2.46 (2.44). The mean of WHZ at T7 was -2.51 (2.29) vs -1,99 (2.49). There was an increase in each group (P=0.009), but the difference was not significant (P=0.584). Complications occurred in 13.3% of subjects in the control group and 66.7% in the home EN group. There was a significant WHZ change affected by complications, but the change was not significant (P=0.186). We concluded that home enteral nutrition had the same effectiveness as in the hospital.